Development and Delivery of a Novel Interdisciplinary Online Course Focused on Pandemics and COVID-19 - Brittany Bates; Daniel Thoryk; Ryan Augustine (Ohio Journal of Public Health, 2024)
Misinformation regarding COVID-19 has clouded the judgment and perspectives of many individuals. At Ohio Northern University, an interdisciplinary online elective course was developed to allow students the opportunity to gain evidence-based insight about the far-reaching implications of pandemics, with a specific focus on COVID-19. This course is open to any undergraduate student at the university without any prerequisites; however the majority of enrolled students come from the pharmacy and nursing programs. This paper describes the development, delivery, and assessment methods of this course. Course evaluation and modifications have allowed this course to evolve over time and remain a well-enrolled course at Ohio Northern University.
Keywords: Interdisciplinary education; Pandemic; Online course design; Misinformation; Public health education; Pharmacy professional elective